Creatinine Clearance in Patients with Obstructive Sleep Apnea - Seda Beyhan Sagmen; Nesrin Kiral; Ali Fidan; Elif Torun Parmaksiz; Coskun Dogan; Sevda Comert (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2021)
During an apnea, hemodynamic complications such as hypoxemia, a rise in systemic and pulmonary arterial pressure, and changes in heart rate occur in patients with obstructive sleep apnea (OSA). Potential mechanisms of OSA-associated renal dysfunction include renal hypoxia, hypertension, endothelial dysfunction. Hypertension is common in patients with OSA. This study aims to assess OSA patients' renal functions and investigate the creatinine clearance (CC) values across OSA patients with and without hypertension. The study included 530 individuals with OSA and 60 individuals with an apnea-hypopnea index (AHI) of 0.05). A statistically significant difference was detected in urea and creatinine levels between the OSA and control groups (p=0.005; p=0.012). Creatinine clearance decreases in patients with OSA in the presence of HT. Patients with OSA often experience cardiovascular disorders, and glomerular endothelial dysfunction occurs in OSA patients.